1998
DOI: 10.1152/ajpgi.1998.275.5.g1202
|View full text |Cite
|
Sign up to set email alerts
|

Supramaximal CCK and CCh concentrations abolish VIP potentiation by inhibiting adenylyl cyclase activity

Abstract: Exocrine pancreatic secretion stimulated by vasoactive intestinal polypeptide (VIP), which acts through the adenylyl cyclase-cAMP pathway, is potentiated by stimulation with other secretagogues such as CCK and carbachol (CCh). However, the potentiating effect is abolished by the same secretagogues at supramaximal concentrations. In the present study, we examined the mechanisms by which supramaximal concentrations of CCK octapeptide (CCK-8) or CCh reduce the VIP-induced potentiation of amylase secretion from is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
3
9
0
1
Order By: Relevance
“…Basal values in OO and C rats were similar between them and comparable to those described in the literature [29,30]. This contrasts with the results of basal Ca 2+ concentration.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Basal values in OO and C rats were similar between them and comparable to those described in the literature [29,30]. This contrasts with the results of basal Ca 2+ concentration.…”
Section: Discussionsupporting
confidence: 79%
“…The dose-response curve for ACh-induced amylase release in pancreatic acinar cells is typically bell-shaped, reaching a maximum at around 1 AM [29,34]. We also observed the strongest secretory effect at 1 AM ACh in both groups.…”
Section: Discussionsupporting
confidence: 50%
“…CCK-8 or CCh induced PKD1 phosphorylation and activation at the concentration as low as 0.1 nM or 1 M, respectively, a physiological level of CCK-8 or CCh that causes maximal digestive enzyme secretion. The maximal effects of these agonists on PKD1 were achieved at 10 -100 nM CCK-8 or at 100 -1,000 M CCh, i.e., at their supramaximal concentrations that cause inhibition of enzyme secretion and activation of the inflammatory response (2,8,9,51). These results indicate that PKD1 is activated by CCK-8 and CCh at both physiological and pathological doses.…”
Section: Cck-8 and Cch Induce Both Pkd1 Phosphorylation/activation Anmentioning
confidence: 76%
“…A later study demonstrated that PKA is responsible for the modulation of Ca 2+ - and PKC-evoked amylase secretion in permeabilized rat pancreatic secretion [4]. Supramaximal concentrations of CCK or carbachol, by contrast, abolish VIP potentiation by inhibiting AC activity through activation of PKC [58]. …”
Section: Role Of Ac In the Regulation Of Digestive Systemmentioning
confidence: 99%
“…In the past years, the hypothesized AC expression profile in pancreatic exocrine cells came primary from studies that use pharmacologic stimulators and inhibitors of intracellular signals [58,59]. Recently, the expression profile of the transmembrane AC isoforms in intact mouse pancreas, isolated pancreatic acini and sealed duct fragments was establishsed [36].…”
Section: Role Of Ac In the Regulation Of Digestive Systemmentioning
confidence: 99%